BIOAKTIVITAS EKSTRAK DAUN JERUK PURUT (CITRUS HYSTRIX DC) TERHADAP RAYAP TANAH (COPTOTERMES CURVIGNATHUS HOLMGREN) - fariq, Al; Diba, Farah; hati, Mufli (JURNAL HUTAN LESTARI, 2015)
Kaffir lime leaves (Citrus hystrix DC) has the potential to be used as a natural preservative especially an anti-termites. The study aims to evaluation the toxicity of extract of leaves C. hystrix against subterranean termites Coptotermes curvignathus Holmgren and to determine the optimal concentration of extract lime leaves on subterranean termite activity. Lime leaves were extracted using maceration method with methanol. Level of concentration were 0%, 2%, 4%, 6%, 8% and 10%. Filter paper soaked at each concentration thengive as a food source to subterranean termites. Bioassay tests were carried out for 21 days. Then mortality and filter paper weight loss was measured. The results showed the concentration level of 10% has the highest termite mortality with average value of 100% and has the lowest value of filter paper weight loss with a average value 13.48%. However, the optimal concentration was achieved at 8% due to the mortality rate reached 94% and the level of termite activity was classified as very strong. Keyword: Bioactivity anti-termites Citrus hystrix DC, Coptotermes curvignathus Holmgren, Methanol extract.